PERAN ORANGTUA DALAM PERKEMBANGAN HIDUP ROHANI REMAJA - Ona Sastri Lumban Tobing (IN VERITATE LUX, 2020)
Family is a form of life partnership that is confirmed through the sacrament of marriage, in which husband and wife form a bond in the process of personal maturation and are open to the birth of children. As a sphere of life in the community of life, the family is a small institution of the Church which is filled with spiritual education. The development of the times and the many demands of life that must be met sometimes make parents less aware that teenagers need attention not only in terms of economic needs, formal education but also how teenagers are in a new environment in the modern sphere. So the role of parents is very important in the growth and development of teenagers, especially instilling the values of spiritual education for teenagers. Parents have noble roles and responsibilities as teachers, priests and shepherds. Parents educate, teach, train and become the first teachers of faith for their children. Parents are the first priests to instill the values of faith, teaching and spiritual life in children. Parents as shepherds are leaders who direct children and provide their children's needs. However, currently many parents still lack the knowledge, understanding, awareness and skills to be teachers, priests and shepherds for their children. The method used in this research uses a combination of Library Research and qualitative research by using and reviewing books and informant interviews related to the role of parents in the development of teenagers' spiritual lives.